Renal stone disease. (September 2019) - Ferraro, Pietro Manuel; Robertson, William; Unwin, Robert
Abstract: Renal stone disease (urolithiasis, nephrolithiasis) covers many conditions causing kidney, ureteric or bladder stones. These include metabolic and inherited disorders, anatomical defects of the upper or lower urinary tract, and chronic urinary infection. However, most cases of renal stones are idiopathic. They present with loin or abdominal pain, and visible or non-visible haematuria; this is followed by eventual passage of a stone and resolution or the need for further investigation and intervention. Renal stones often recur and it is important to identify the underlying cause, particularly as stones can be related to diet and lifestyle, and are often associated with hypertension or diabetes mellitus. Although clinical management is largely surgical and can seem simple, the increasing prevalence of renal stone disease in developed countries is becoming a significant economic and health burden.